A Power-Efficient High-Throughput 32-Thread SPARC Processor. - Leon, A. S. (IEEE Journal of solid state circuits)
This first generation of "Niagara" SPARC processors implements a power-efficient Chip Multi-Threading (CMT) architecture which maximizes overall throughput performance for commercial workloads. The target performance is achieved by exploiting high bandwidth rather than high frequency, thereby reducing hardware complexity and power. The UltraSPARC T1 processor combines eight four-threaded 64-b cores, a floating-point unit, a high-bandwidth interconnect crossbar, a shared 3-MB L2 Cache, four DDR2 DRAM interfaces, and a system interface unit. Power and thermal monitoring techniques further enhance CMT performance benefits, increasing overall chip reliability. The 378-mm2 die is fabricated in Texas Instrument's 90-nm CMOS technology with nine layers of copper interconnect. The chip contains 279 million transistors and consumes a maximum of 63 W at 1.2 GHz and 1.2 V. Key functional units employ special circuit techniques to provide the high bandwidth required by a CMT architecture while optimizing power and silicon area. These include a highly integrated integer register file, a high-bandwidth interconnect crossbar, the shared L2 cache, and the IO subsystem. Key aspects of the physical design methodology are also discussed